(untitled) (Bangladesh Journal of Medical Science, 2012)
Peritonsillar abscess is a known complication of tonsillitis.The patient usually present with typical symptoms of odynophagia, fever and difficulty in mouth opening. The diagnosis is established by clinical examination that commonly revealed unilateral peritonsillar swelling. Aspiration of pus will confirm the diagnosis. We report an atypical presentation of peritonsillar abscess case which presented with dysphagia without fever, odynophagia and trismus. Keywords: Peritonsillar abscess; atypical; presentation DOI: http://dx.doi.org/10.3329/bjms.v10i4.9505 BJMS 2011; 10 (4): 293-295